The Bending Effect of Single-Mode Optical Fiber at Long Distance from Laser Source on the Spot Laser (Journal of the College of Basic Education, 2022)
The bending effect on coherent light in the single mode optical fiber wasstudied. In this work single mode optical fiber made from silica and turn overcylinders with different diameters (3, 5 and 10) cm to obtain variable bendingdiameter of fiber was used. Also, diode laser with wavelength (630-680) nm andmax. power (5) mw was used as laser source. The image of spot laser for eachturn was captured by digital camera connected with computer and at constantlong distance (247) cm from laser source.